2019
DOI: 10.30782/jrvm.620868
|View full text |Cite
|
Sign up to set email alerts
|

Ceylanlarda (Gazella subgutturosa) Mandibulanın Üç Boyutlu Rekonstrüksiyonu ve Morfometrik Yapısı: Bir BT Çalışması

Abstract: Bu çalışmada ceylan (Gazella subgutturosa) mandibula'sının anatomik, morfometrik ve volümetrik özellikleri bilgisayarlı tomografi (BT) ve üç boyutlu (3D) yazılım programı kullanılarak tespit edildi. Bu amaçla 10 adet (5 erkek, 5 dişi) ceylan kafası kullanıldı. Kafaların 64 dedektörlü BT cihazında 80 kv, 200 MA, 639 mGY ve 0.625 mm kesit kalınlığında görüntüleri alındı. Her bir deneğin mandibulaya ait tarama görüntüleri özel bir 3D yazılım programı yardımıyla üç boyutlu modellere dönüştürülerek rekonstrükte edi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…The GOC-ID value was determined as 157.6 ± 22.5 mm in Mehraban sheep (Karimi et al, 2012) While Yilmaz and Demircioglu (2019) reported that the mandible volume in gazelles was 40.36 ± 6.03 cm 3 in males and 37.98 ± 4.69 cm 3 in females, Güzel et al (2023) reported this value as 45.79 ± 1.33 cm 3 in rams and 44.03 ± 0.18 cm 3 in ewes in Hamdani sheep. In the present study, the volume was determined as 43.54 ± 1.68 mm 3 in males and 42.03 ± 0.18 mm 3 in females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GOC-ID value was determined as 157.6 ± 22.5 mm in Mehraban sheep (Karimi et al, 2012) While Yilmaz and Demircioglu (2019) reported that the mandible volume in gazelles was 40.36 ± 6.03 cm 3 in males and 37.98 ± 4.69 cm 3 in females, Güzel et al (2023) reported this value as 45.79 ± 1.33 cm 3 in rams and 44.03 ± 0.18 cm 3 in ewes in Hamdani sheep. In the present study, the volume was determined as 43.54 ± 1.68 mm 3 in males and 42.03 ± 0.18 mm 3 in females.…”
Section: Discussionmentioning
confidence: 99%
“…Karimi et al, 2012), 94.20 ± 7.65 mm in Hemshin sheep(Dalga et al, 2017), 108.68 ± 2.36 mm in Hasmer sheep(Özüdoğru, İlgün, & Özdemir, 2019), 110.97 ± 2.95 mm in Konya merino(Özüdoğru et al, 2019b), and 109.86 ± 5.56 mm in Kosovo Bardhoka breed(Özkan et al, 2020) Yilmaz and Demircioglu (2019). stated in their study on gazelle mandible that there was a statistical significance between sexes in the GOV-CR data; similar toÖzkan et al (2020)'s study in the Kosova Bardhoka breed, it was determined in the pres-…”
mentioning
confidence: 99%
“…With the advancement of technology, besides bone morphometric measurements, CT and three‐dimensional modelling of bones are also performed (Berge & Goularas, 2010; Brenton et al, 2007; Freitas et al, 2011; Moselhy & Mahdy, 2019; Ohlerth & Scharf, 2007; Özkadif, 2015; Sukumar et al, 2012; Yilmaz et al, 2020; Yilmaz & Demircioğlu, 2019). Although there have been morphological (Yilmaz, 1998) and morphometric (Angelici et al, 2003; Corbet & Jones, 1965; Mohamed, 2011; Mori et al, 2019) studies on the porcupine skull, three‐dimensional modelling of the skull is performed for the first time with the present study.…”
Section: Discussionmentioning
confidence: 99%
“…In mammals, the mandible is mostly made of cortical bone and is physiologically equipped with teeth. The anatomy of the mandible is very important for both phylogenetic and biomechanical analyses (Szabelska et al, 2017; Yilmaz & Demircioğlu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The 2D cross‐sectional images obtained can be transferred to the software in different file formats and three‐dimensional (3D) models can be created. Images of the anatomic structure that is desired to be examined by using various software can be examined, measured or divided (Demircioglu & Gezer, 2020; Freitas, Noritomi, & Silva, 2011; Özkadı̇f & Eken, 2015; Sergovich, Johnson, & Wilson, 2010; Yilmaz & Demircioglu, 2021). 2D conventional imaging methods have disadvantages such as magnification, superposition and minimization.…”
Section: Introductionmentioning
confidence: 99%